2016
DOI: 10.3389/fvets.2016.00105
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Foot-and-Mouth Disease Virus during the Incubation Period in Pigs

Abstract: Understanding the quantitative characteristics of a pathogen’s capability to transmit during distinct phases of infection is important to enable accurate predictions of the spread and impact of a disease outbreak. In the current investigation, the potential for transmission of foot-and-mouth disease virus (FMDV) during the incubation (preclinical) period of infection was investigated in seven groups of pigs that were sequentially exposed to a group of donor pigs that were infected by simulated-natural inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The analyses presented herein are based on data derived from a series of three complementary experimental studies, defined herein as Study A, B, and C (Table 1 ) ( 8 , 23 , 24 ). These studies were originally designed for the purpose of investigating FMDV pathogenesis and transmission in pigs, with minor variation in study design across experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses presented herein are based on data derived from a series of three complementary experimental studies, defined herein as Study A, B, and C (Table 1 ) ( 8 , 23 , 24 ). These studies were originally designed for the purpose of investigating FMDV pathogenesis and transmission in pigs, with minor variation in study design across experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Study C (Table 1 ) was designed to determine the transition from latent to infectious phases in IOP inoculated pigs ( 23 ). A previous publication based on this study provided descriptive analyses of FMDV infection dynamics following contact-exposure, and demonstrated that transmission of FMDV occurred prior to the onset of clinical signs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether cattle, wild cloven-hoofed animals or mice are directly infected by SVV or not, is still unknown. FMDV, another picornavirus that also affects pigs and causes similar vesicular disease, spreads by direct contact or exposure to aerosolized virus, and it also affects various wild cloven-hoofed animals ( Rweyemamu et al, 2008 ; Stenfeldt et al, 2016 ). However, many aspects of SVV infection characteristics, host range, and epidemiology remain unknown.…”
Section: Epidemiologymentioning
confidence: 99%
“…Infectiousness in FMDV‐inoculated pigs starts 24 hr after inoculation but before the first clinical signs of viremia appear (Stenfeldt, Pacheco, et al, ). In contrast, FMDV‐inoculated cattle are not infectious until on average 0.5 days after clinical signs appear (Charleston et al, ) although virus shedding also occurs during pre‐clinical and early recovery stages (Nelson et al, ; Orsel et al, ).…”
Section: Discussionmentioning
confidence: 99%